COVID-19 + Brexit - Calzada, I (Euskal Editorea SL, 2020)
This dissemination article published in the Basque newspaper BERRIA examines the current post-BREXIT status alongside the post-COVID-19 aftermath. The article elucidates that both phenomena are mutually reinforced in a uncertain dynamic that is increasingly intertwined with the AI disruption. The article argues that the future of the UK will lie in the Economic European Space (EES) alongside Iceland, Liechtenstein and Norway. Nonetheless, this pathway may not even seem likely in the short-term and without turbulent political maneuvers and tactics. Ultimately, the article concludes with the notion of the pandemic citizenship as the similar global pattern affecting citizens worldwide.